Effects of Instrumented Assisted Soft Tissue Mobilization (IASTM) Technique Versus Stretching on Ililotibal Band in Patients with Anterior Knee Pain - Humera Mubashar, Danish Hassan, Mehak Bushra, Zaryyab, Abdul Rahman, Aqsa Manahil (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anterior knee pain is caused by many factors iliotibial band tightness is one of cause of knee pain. The repeated hip abduction or postural imbalance usually results in contracture and tightness of the iliotibial band. Soft tissue mobilization is hypothesized as one of effective treatment. Instrumented assisted soft tissue (IASTM) technique is a soft tissue mobilizing technique and have remarked effects. Objective: This study’s objective was to assess how well IASTM improved hip adduction range of motion (ROM). Methodology: This study was quasi experimental trial. And duration for this study was 6 month after the approval of synopsis. Sample of total 46 with knee pain was recruited in two groups. Non- probability convenience sampling technique was used. Total sample size was 30(15 each group). Subjects were allocated into 02 Groups. Inclusion criteria were Age 25 to 50 years and patients with Anterior Knee Pain, Patients of both genders. One group received IASTM and other group received self stretching for flexor group. Outcome was measured on NPRS, goiniomere and lower extremity function scale (LEFS) and values were be taken at baseline and after one week of treatment and then at third week of treatment. The data was analyses using SPSS v 25. Results: The results shows no significant improvement in pain, LEFS and hip abduction range between both groups comparison but both treatments IASTM and stretching exercises shows significant results within each group.The individuals in the GT group showed better hip abduction strength after three treatment sessions. Furthermore, after the one-month follow up, the gain in strength persisted. HoweverThere was no significant difference statistically in hip adduction ROM or VAS scores for pain and function between both the control group and graston (GT) group. Practical application :This study is going to help physical therapist and instrumented assisted soft tissue mobilization practitioners that how Graston technique and stretching effective in terms of decreasing pain, improving flexibility and lower extremity functions in patient with illiotibal band tightness having anterior knee pain. Conclusion: IASTM technique and stretching was equally effective in terms of decreasing pain, improving flexibility and lower extremity functions in patient with illiotibal band tightness having anterior knee pain. Keywords: instrumented assisted soft tissue mobilization, iliotibial band, ant knee pain, soft tissue mobilization.